Investigation of shift registers with nonlinear feedbacks as combining and filtering functions - Poluyanenko, N.; Potii, O. (Radiotekhnika, 2018)
The cryptographic resistance of the stream cipher is determined, among other things, by the ability of the generated pseudo-random sequence (PRS) to resist analytic attacks. One of the main components of the PRS streaming cipher generation algorithm is Boolean functions combining and filtering. The possibility of using shift registers with nonlinear feedbacks of the second order is considered, a sequence of the maximum period as a combining or filtering function is formed. The main indicators of cryptographic stability of such functions are investigated, namely: balance, presence of inhibitions, correlation immunity and nonlinearity. Experimental indications of correlation immunity and nonlinearity for all М-РЗНЗЗ of the second order with a dimension of up to 9 cells inclusive are investigated and presented.